Copper(0)-Catalyzed Reductive Coupling of Disulfurating Reagents and (Hetero)aryl/Alkyl Halides - Chen, Wang; Xu, Jiuwen; Rao, Weidong; Shen, Shu-Su; Yang, Zhao-Ying; Ackermann, Lutz; Wang, Shun-Yi (Organic letters, 2024)
Herein, we reported a copper(0)-catalyzed reductive coupling of disulfurating reagents and (hetero)aryl/alkyl halides. Copper(0) can be directly inserted into tetrasulfide and then undergoes reductive coupling with (hetero)aryl Iodides to construct disulfide. The method features the unprecedented use of copper(0)-catalyzed disulfurating reagents (tetrasulfides) in cross-coupling chemistry and is convenient with broad substrate scopes, even applicable to different halogenated hydrocarbons. It is worth noting that the methodology is practical with the late-stage modification of bioactive scaffolds of pharmaceuticals. In the meantime, the synthesis of disulfides is successfully achieved on a gram scale, indicating the approach is highly valuable.